Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1164/ajrccm.162.2.9909105
|View full text |Cite
|
Sign up to set email alerts
|

Production of Endogenous Nitric Oxide in Chronic Obstructive Pulmonary Disease and Patients with Cor Pulmonale

Abstract: Exhaled nitric oxide (NO) production in stable chronic obstructive pulmonary disease (COPD) has been loosely related to the severity of illness, being significantly reduced in the most severe cases. Pulmonary hypertension is associated with lower NO output from the lung. In this study expired NO was measured in patients with severe stable COPD with or without cor pulmonale (CP). Echocardiographic estimates of right heart function, lung function, diffusion capacity, respiratory muscle strength, and arterial blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…There is some evidence, however, that the concentration of NO in expired air is lower in patients with more severe COPD. CLINI et al [93] investigated the relationship between expired NO and right-ventricular function in a group of 34 patients with COPD, showing that echocardiographic estimates of Ppa and right-ventricular function were significantly correlated with expired NO concentration. Patients with right-ventricular dysfunction had lower NO concentration in expired air, suggesting that these patients might have either an impaired release or reduced diffusion of NO from the endothelium into the airways [93].…”
Section: Analysis Of Expired Airmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence, however, that the concentration of NO in expired air is lower in patients with more severe COPD. CLINI et al [93] investigated the relationship between expired NO and right-ventricular function in a group of 34 patients with COPD, showing that echocardiographic estimates of Ppa and right-ventricular function were significantly correlated with expired NO concentration. Patients with right-ventricular dysfunction had lower NO concentration in expired air, suggesting that these patients might have either an impaired release or reduced diffusion of NO from the endothelium into the airways [93].…”
Section: Analysis Of Expired Airmentioning
confidence: 99%
“…It should be noted, however, that the exact origin of NO in expired air is uncertain. Nonetheless, the idea that markers of endothelial function could be analysed in expired air and this might provide information about pulmonary vascular function [93] is attractive and should deserve further investigation.…”
Section: Analysis Of Expired Airmentioning
confidence: 99%
“…The hypoxic pulmonary vasoconstrictor response is an important adaptive mechanism in human physiology, shunting blood away from hypoxic regions toward better-ventilated areas of the lung, thus improving ventilation-perfusion matching within the lung. Pulmonary vascular remodeling in response to hypoxia is also mediated by a number of other factors including nitric oxide, 9 endothelin, 10 serotonin, and hypoxia inducible factor-1. The role of inflammatory mediators has become increasingly accepted.…”
Section: Pulmonary Vascular Disease In Respiratory Illnessmentioning
confidence: 99%
“…Indeed Hyde et al [25] suggested that changes in NO in the exhaled gas represents changes in diffusing capacity rather than changes in NO production in the airways. Clini et al [40] came to similar conclusions. Production of NO from lung tissue into the alveolar space is likely to increase during inflammatory conditions such as asthma, which can lead to increase NO in the exhaled air.…”
Section: Discussionmentioning
confidence: 64%